Model Sistem Perparkiran Kendaraan di Bandar Udara Sentani Jayapura - Johanis Taran; Sakti Adji Adisasmita; Mubassirang Pasra (Jurnal Penelitian Enjiniring, 2018)
This study aims to determine the characteristics of existing conditions, the perceptions of respondents of parking users, and the need for parking space based on the highest accumulation rate. Methods of data collection are done by a direct survey to the field to record the number and time of the vehicle when entering and exiting and survey the perception of respondents parking users by using questionnaires. The result of data analysis shows that the average daily vehicle volume is 2649 with the highest average accumulation is 639. Average vehicle duration per day is 1.65 vehicles/hour, average parking turn over value of 6 and parking index of 1.48%, this means that on average per day only 6 vehicles alternately occupy 1 parking space. Low parking turnover is due to the very high vehicle volume with a long parking duration but parking space available is very less ie as many as 432 parking spaces, so that the impact on over-capacity parking that can be seen from the high number of parking accumulation that occurred at the peak hour is at 12:30 to 13:00 pm. Of 313 respondents of parking users who responded to 16 parameters about the characteristics of parking lots, 5% stated very worthy, 23% stated feasible, 57% said it was not feasible, 11% expressed bad, and 5% said very badly. The model of parking space needs shows the relationship between vehicle volume and accumulation of R = 0,67 with the modely = 0,06972x + 454,07, Capacity and accumulation of R = 0,62,with the model y = 0,0696x + 454,07, Duration and accumulation of R = 0,60 with the model y = -91,72x + 789,49.